2011
DOI: 10.1021/ie100368t
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Breakage and Coalescence Model Parameters in a Steady-State Batch Agitated Dispersion

Abstract: The highly dynamic behavior of liquid−liquid dispersions in reaction and separation operations still defies accurate and experimentally validated modeling. This behavior is characterized by simultaneous dropsize and operating conditions dependent drop breakage and coalescence, which strongly influence both the hydrodynamics and the reaction yield and selectivity, or separation performance, of such systems. This dynamic character of the behavior is present and of critical importance even at steady state, and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…/j.ces.2016.08.028 21 simulations using the adapted parameter sets of Coulaloglou and Tavlarides (1977) and Kamp and Kraume (2015) result in nearly identical steady states of 32 although the parameters 1 and 1 vary by several orders of magnitude. But the ratio between the parameters 1 / 1 and the value of 2 do not vary considerably which confirms the findings of Ribeiro et al (2011).…”
Section: Transfer To Droplet Swarmssupporting
confidence: 86%
See 2 more Smart Citations
“…/j.ces.2016.08.028 21 simulations using the adapted parameter sets of Coulaloglou and Tavlarides (1977) and Kamp and Kraume (2015) result in nearly identical steady states of 32 although the parameters 1 and 1 vary by several orders of magnitude. But the ratio between the parameters 1 / 1 and the value of 2 do not vary considerably which confirms the findings of Ribeiro et al (2011).…”
Section: Transfer To Droplet Swarmssupporting
confidence: 86%
“…Numerical parameters are needed to apply the population balance equation to a specific system. In literature a broad variety of parameter sets can be found (Maaß, 2011;Ribeiro et al, 2011) because interdependencies between the numerical parameters exist (Ribeiro et al, 2011). For that reason, different parameter combinations can lead to the same ratio between drop breakage and coalescence rate which results in identical simulations (at least in steady state).…”
Section: Transfer To Droplet Swarmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different might be attributed by the different approaches in determining the parameters although most of the approaches have been based on trial and error attempts to reproduce experimental results. Ribeiro et al, (2011) developed an optimization tool which was tested on the determination of constants in the models of Coulaloglou and Tavlarides (1977) . The work showed that the constants values obtained by the authors are in agreement with the older values reported in literature.…”
Section: Population Balance Equationmentioning
confidence: 55%
“…Drop coalescence is one of the processes that is responsible for the evolution of drop sizes and without coalescence, real steady state could not be achieved . The relative motion between drops result in collisions which lead to coalescence .…”
Section: Mechanism Of Drop Formationmentioning
confidence: 99%